Post-Humanism and the Future of Humanity in Light of Technological Enhancement of the Body - Mohamed TAHIR & Abdelghani ALIOUA (Akofena)
Abstract: This research paper aims to highlight the background of the transformation that has affected biotechnology, shifting its applications in the medical field—particularly after its integration with nanotechnology, artificial intelligence, and informatics (NBIC)—into a force capable of shaping the future of humanity. This transformation goes beyond addressing physical and medical disorders affecting the human body; it extends to enhancing and developing human intellectual and physical capacities (a stronger body, longer lifespan, superior intelligence, etc.) while pursuing a shift in human nature from being a created being to a mechanized entity. This trajectory poses a significant threat to the future of humanity.